2001
DOI: 10.1007/s005420000083
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanical three-axial tactile force sensor for micromaterial characterisation

Abstract: A three-axial tactile force sensor for the investigation of micromechanical structures has been developed using silicon micromachining technology. The sensor is capable of performing mechanical micro material characterisation such as the determination of the spring constant of complex micromechanical structures. Another application for this sensor is dimensional metrology where it has been tested as a 3D probe in a test set-up for coordinate measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…However, it is very difficult to precisely measure the shapes of micro-holes that have large length/diameter (L/D) ratios because of the difficulties encountered during probe fabrication and the complexities involved in employing a sensing method that uses a small measuring force. Many studies have been reported on micro-hole measurement techniques employing a variety of probes such as optical probes [1][2][3], vibroscanning probes [4,5], vibrating probes [6][7][8][9][10][11][12], tunneling effect probes [12,13], opto-tactile probes [14], fiber probes [15,16], optical trapping probes [17], and diaphragm or flexure based probes using an elastic mechanism [18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is very difficult to precisely measure the shapes of micro-holes that have large length/diameter (L/D) ratios because of the difficulties encountered during probe fabrication and the complexities involved in employing a sensing method that uses a small measuring force. Many studies have been reported on micro-hole measurement techniques employing a variety of probes such as optical probes [1][2][3], vibroscanning probes [4,5], vibrating probes [6][7][8][9][10][11][12], tunneling effect probes [12,13], opto-tactile probes [14], fiber probes [15,16], optical trapping probes [17], and diaphragm or flexure based probes using an elastic mechanism [18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…precision, which focus on the development of acquisition probe and positioning systems [3,4]. Some of the micro/nano coordinate measurement machines developed by PTB (The PhysikalischTechnische Bundesanstalt) use the piezo-resistors as the probes which are attached by the silicon thin film [5][6][7][8]. Due to the internal stress of the silicon thin film, it is difficult to evaluate the mechanical and thermal properties of the probes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, three-axis piezoresistive force sensors have been described [8,9,10,11]. These sensors are designed for measuring forces up to a single Newton.…”
Section: Introductionmentioning
confidence: 99%